Validation of a prototype DiodeAir for small field dosimetry. (19th March 2015) - Underwood, T S A; Thompson, J; Bird, L; Scott, A J D; Patmore, P; Winter, H C; Hill, M A; Fenwick, J D
Abstract: Standard commercial diode detectors over-respond within small radiation fields, an effect largely attributable to the relatively high mass-density of silicon. However, Monte Carlo studies can be used to optimise dosimeter designs and have demonstrated that 'mass-density compensation'—for example, introducing a low-density air-gap upstream of a diode's high-density silicon volume—can substantially improve instrument response. In this work we used egs_chamber Monte Carlo simulations to predict the ideal air-gap thickness for a PTW 60017 unshielded diode detector. We then developed a prototype instrument incorporating that air-gap and, for a 6 MV linac, tested it experimentally against EBT3 film. We also tested a further three prototypes with different air-gap thicknesses. Our results demonstrate that for a 10 × 10 cm 2 reference field the DiodeAir, a PTW 60017 diode with a built-in air-gap of 1 mm, has on-axis correction factors near unity. Laterally the DiodeAir performs very well off-axis and reports FWHM and penumbra values consistent with those measured using EBT3. For PDD measurement, the performance of the DiodeAir matches that of the original PTW 60017. The experimental focus of this work was 6 MV but we also simulated the on-axis response of the DiodeAir within 15 MV beams and found that our modification proved robust to this substantial increase in beam energy. However, the original diode 60017 does exhibit low energy scatter dependencies and may over-respond to high linac dose-rates such that applying the mass-density compensation method to an alternative instrument (particularly a diamond detector) could ultimately take us even closer to the small-field ideal.